Identification and molecular characterization of Babesia species in brown (Parahyaena brunnea), striped (Hyaena hyaena) and spotted hyaenas (Crocuta crocuta) - Oosthuizen, Marinda C. (University of Pretoria, 2015)
Mini-dissertation (MSc)--University of Pretoria, 2014.